STUDY OF THE SITUATION IN THE PROCESS OF TRANSLATION (Scientific journal of the Fergana State University, 2024)
This article is about the significance of the situation in the process of translation, its transition from the original language to the translated language, and the opinions of scientists about the situational-denotative method, which is a model of translation, are given. The study provides full information about this method and its analysis. In addition, the article shows the construction and its difference from the sentence, its specific features. In particular, a construction is a speech unit, which is a linguistic expression of a situation. A sentence is a language unit that expresses the relation of subject and verb. Construction is a broad concept in relation to the sentence, namely, it is important for the translator to understand the situation correctly in the translation and to have knowledge about the construction when translating it into another language.